Mo2C interface layer: effect on the interface strength and cutting performance of diamond/Fe-Ni-WC composites - Xinyue Mao; Qingnan Meng; Mu Yuan; Sifan Wang; Shiyin Huang; Baochang Liu (Journal of Materials Research and Technology, 2023)
The weak interfacial strength between Fe-based matrix and diamonds causes diamond particles to fall off prematurely, significantly affecting the cutting efficiency of diamond composites. This work aimed to optimize the interfacial microstructure and mechanical properties of the diamond/Fe-Ni-WC composites by coating a Mo2C layer on the diamond particles. The Mo2C-coated diamonds were prepared via the molten salt method. Diamond/Fe-Ni-WC composites were sintered by the hot-pressing process under a vacuum. The bending strength of composites with Mo2C-coated diamonds was improved from 804 to 996 MPa with the increased coating time. The energy dispersive spectroscopy scanning indicated that the Mo2C coating layer changed the interfacial composition between the matrix and the diamonds from Fe–C alloy to Mo2C, improving the interface strength. Moreover, the diamond protrusion heights of composites were raised by adding a Mo2C interface, resulting in an improvement in the cutting efficiency of impregnated diamond tools.